2019
DOI: 10.1002/1878-0261.12555
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Down‐regulation of long noncoding RNA PVT1 inhibits esophageal carcinoma cell migration and invasion and promotes cell apoptosis via microRNA‐145‐mediated inhibition of FSCN1

Abstract: Accumulating evidence has established that long noncoding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) is a tumor regulator in many cancers. Here, we aimed to investigate the possible function of lncRNA PVT1 in esophageal carcinoma (EC) via targeting of microRNA‐145 (miR‐145). Initially, microarray‐based gene expression profiling of EC was employed to identify differentially expressed genes. Moreover, the expression of lncRNA PVT1 was examined and the cell line presenting with the highest level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…[22][23][24] Plasmacytoma variant translocation 1 (PVT1), a lncRNA, is abnormally expressed in numerous cancer cells and tissues. 25,26 In particular, PVT1 acts as an oncogene in tumor metastasis and growth. [27][28][29] Nevertheless, the molecular mechanism of PVT1 in cancer evolution remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Plasmacytoma variant translocation 1 (PVT1), a lncRNA, is abnormally expressed in numerous cancer cells and tissues. 25,26 In particular, PVT1 acts as an oncogene in tumor metastasis and growth. [27][28][29] Nevertheless, the molecular mechanism of PVT1 in cancer evolution remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Pvt1 oncogene (PVT1) with a confidence score of 25.4 is ranked on the second place for the EACspecific prognostic lncRNAs. Based on the strategy of competitive endogenous RNA (ceRNA) networks [15], overexpression of PVT1 correlates with a poor prognosis [16] or a fast tumor progression [17] in esophageal cancer patients or in ESCC [18] In this study, PVT1 was indicated as an EAC-specific lncRNA since it does not belong to the intersection set between lncRNAs for these two subtypes. CDKN2B antisense RNA 1 (CDKN2B-AS1), also known as ANRIL, was on the top of this list (i.e., cancer related EAC-specific prognostic lncRNAs), however, only three studies [19][20][21] have addressed its association with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…29 In esophageal carcinoma, PVT1 promoted cancer progression by regulating miR-145/VEGF pathway. 30 Moreover, PVT1 was reported to have clinical signi cance and found to be associated with malignant progression in ovarian cancer. [31][32][33] However, further investigation for elucidating its detailed involvement in HGSOC tumorigenesis was required.…”
Section: Discussionmentioning
confidence: 99%